C-Reactive Protein Level as a Novel Serum Biomarker in Sarcopenia - Shangjin Lin; Xiuxiu Chen; Ying Cheng; Hou Huang; Fengjian Yang; Zhijun Bao; Yongqian Fan (Mediators of Inflammation)
Background. The role of C-reactive protein (CRP), an inflammatory marker, in the development of sarcopenia remains uncertain. Methods. This cross-sectional research involved the enrollment of 207 patients, classified into two groups: 74 patients with sarcopenia and 133 patients without sarcopenia. Clinical data of the participants, including hand grip strength, walking speed, appendicular lean mass (ALM), and calf circumference, were collected and recorded. We evaluated the extent to which CRP levels are associated with the risk of sarcopenia using both univariate and multivariate logistic regression models. Besides, the correlation between CRP levels, hand grip strength, ALM, and walking speed was examined using the Spearman rank correlation test. Moreover, we have employed the Mendelian randomization (MR) analysis technique to explore the causal relationship between CRP levels and the occurrence of sarcopenia. Results. The sarcopenia group showed a higher proportion of older women, with significant differences in anemia prevalence, calf circumference, gait speed, ALM, hand grip strength, and elevated CRP levels compared to the control group. Logistic regression analyses identified CRP as an independent risk factor for sarcopenia (OR: 1.151, 95% CI:1.070−1.238, and P<0.001). Correlation analysis results revealed a noteworthy inverse association with hand grip strength (R = −0.454 and P<0.001), ALM (R = −0.426 and P<0.001), and walking speed (R = −0.431 and P<0.001). MR analysis provided further evidence of a significant detrimental link between genetically predicted CRP levels and essential sarcopenia characteristics, with consistent results across various statistical models. Conclusions. Our study uncovered strong evidence supporting a noteworthy inverse association and causality between CRP concentrations and sarcopenia, indicating that CRP has the potential to serve as a biomarker for sarcopenia.